Enhanced generation of beta cell precursors and functional insulin-secreting cells from human pluripotent stem cells - Bushra Memon (4792767) (2023)
Poster by Bushra Memon (Hamad Bin Khalifa University), Ihab Younis (Carnegie Mellon University in Qatar),  Fadhil Abubaker (Carnegie Mellon University in Qatar), and Essam M. Abdelalim (Hamad Bin Khalifa University)  Background: Human pluripotent stem cells (hPSCs) are excellent tools for studying early human pancreatic development, modeling diabetes and cell therapy. hPSCs have been differentiated in vitro to functional pancreatic beta cells, however, the hPSC-derived beta cells are transcriptionally and functionally dissimilar to adult beta cells. Pancreatic progenitors that co-express PDX1, a master regulator of pancreatic development, and NKX6.1, a transcription factor crucial for development and functionality of beta cells, differentiate to functional, glucose-responsive beta cells both in vitro and in vivo. Pancreatic progenitors have been utilized for the first hPSC-based clinical trial for type 1 diabetic patients. However, in the absence of NKX6.1, the PDX1+ progenitors give rise to non-functional beta cells. Nevertheless, presence of beta cell heterogeneity within the adult human islet indicates existence of multiple, non-conventional routes to beta cell development not yet discovered. Objective: Herein, we aimed to optimize the generation of PDX1+/NKX6.1+ pancreatic beta cell precursors by modulating factors regulating the cellular environment. We also aimed to characterize a novel progenitor population (PDX1-/NKX6.1+), generated using our optimized protocol, and assess their capacity to differentiate into insulin-secreting beta cells.  Methods: Cells were dissociated following endoderm stage and replated at either half or lower densities on fresh Matrigel. hPSCs were differentiated into PDX1+/NKX6.1+ and PDX1-/NKX6.1+ progenitors, which were further differentiated into insulin-secreting cells. The progenitors and beta cells were extensively characterized for gene expression by immunofluorescence, RT-PCR and functional assay. Transcriptome analysis was performed at different stages and compared with profiles of various human pancreatic counterparts. Results: Dissociation of endodermal cells followed by extension of stage 3 with retinoid and FGF signaling as well as hedgehog inhibition, led to increased percentage of PDX1 and NKX6.1 co-expressing progenitors. Upon further differentiation to endocrine stages, the PDX1+/NKX6.1+ progenitors gave rise to NEUROGENIN 3-expressing endocrine progenitors and INSULIN-secreting functional beta cells with high efficiency. On the other hand, PDX1−/NKX6.1+ progenitors formed 3D structures with defined borders, adjacent to the conventional PDX1+/NKX6.1+ progenitors.  PDX1−/NKX6.1+ progenitors showed a similar profile to pancreatic mesenchymal stem cells with high expression of NESTIN, a key marker of pancreatic islet-derived progenitors, in the absence of E-CADHERIN. Transcriptional analysis at the progenitor stage revealed a downregulation of pancreatic epithelial genes and upregulation of neuronal development genes in PDX1−/NKX6.1+ cells in comparison to the PDX1+/NKX6.1+ cells. Interestingly, on further differentiation, PDX1−/NKX6.1+ cells generated mono-hormonal INSULIN+ cells (3D-beta) and activated pancreatic key genes, such as PDX1. The 3D-beta cells secreted C-peptide in response to increased glucose concentrations as well as membrane depolarization indicating they possess functionality and secretory insulin granules. The transcriptome profile of PDX1−/NKX6.1+-derived beta cells was closely like those of human pancreatic islets and purified hPSC-derived beta cells. Conclusion: These findings confirm that modulating cellular environment by dissociating and replating the endodermal cells could enhance the generation of proliferative PDX1+/NKX6.1+ pancreatic progenitors. Our optimized protocol can generate high yields of functional insulin-secreting pancreatic beta cells. Furthermore, PDX1-/NKX6.1+ progenitors provide a novel source of insulin-secreting cells that can serve as a candidate for beta cell therapy for diabetes.